2014
DOI: 10.1037/tep0000031
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and reformulation of outcome evaluation in clinical supervision: Applying the fidelity framework.

Abstract: Although a strikingly diverse range of outcomes have been measured within clinical supervision research, a dominant perspective is that clinical outcomes remain the "acid test" of its effectiveness (Ellis & Ladany, 1997). We question the wisdom of this acid test logic in 2 ways. First, we summarize alternative conceptu alizations of outcome from within the supervision field, highlighting several important reasons for considering clinical benefit as but one of several equally valid, stepwise outcomes. The fidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
2
42
0
4
Order By: Relevance
“…Components in the domains of provider training, treatment receipt and treatment enactment were infrequently reported. This is in contrast to reviews utilizing the NIH Fidelity Framework in other areas that found higher reporting of enactment . It should be noted that one enactment item (Reporting use of a strategy to improve subject performance of intervention skills) was excluded from this review, as adequate reliability could not be obtained.…”
Section: Discussionmentioning
confidence: 97%
“…Components in the domains of provider training, treatment receipt and treatment enactment were infrequently reported. This is in contrast to reviews utilizing the NIH Fidelity Framework in other areas that found higher reporting of enactment . It should be noted that one enactment item (Reporting use of a strategy to improve subject performance of intervention skills) was excluded from this review, as adequate reliability could not be obtained.…”
Section: Discussionmentioning
confidence: 97%
“…Only 19.6% of the studies identified from the forward citation search to report on fidelity were found to address receipt, compared with 33% in a recent review on clinical supervision [85]. Amongst the studies identified, 60.6% assessed receipt in relation to understanding (compared to 0–69% in other reviews [10, 1417]) and 42.4% in relation to performance of skill (39–65% in other reviews [10, 1417]).…”
Section: Discussionmentioning
confidence: 99%
“…Only 18 supervision-client outcome studies were conducted from 1981 to 2006 (Watkins, 2011a), and the vast majority of these studies were marked by several methodological shortcomings. Shortcomings included 1) lack of manuals operationalizing supervision, 2) insufficient documentation of supervisor training, 3) failure to demonstrate supervision integrity, 4) poorly defined and psychometrically weak instruments to measure clinician and client outcomes, 5) very small sample sizes of supervisors and clinicians reducing power for hypothesis testing, 6) inclusion of clinicians unrepresentative of community program service providers, and 7) no comparison or control conditions, random assignment, or routine follow-up assessments (Ellis & Ladany,1997; Ellis et al, 1996; Herschell et al, 2010; Holloway & Neufeldt, 1995; Reisner & Milne, 2014; Roth, Pilling, & Turner, 2010; Watkins, 2011a; Schoenwald et al, 2009). Moreover, none of the studies controlled for the effect of seminars or workshops that preceded supervision.…”
Section: Introductionmentioning
confidence: 99%